FISCAL STRESS IN LOCAL GOVERNMENTS: DO LOCAL REVENUE, DEBT UTILIZATION AND SERVICE LEVEL FLEXIBILITY INFLUENCE? - Nasution, Ichlasul Amin (UIN Sunan Gunung Djati Bandung, 2024)
The purpose of this study was to determine and analyze the effect of local revenue, debt usage and flexibility of local government service levels on fiscal stress in regencies and cities in North Sumatra Province. This study included all 33 districts and cities in North Sumatra Province in three periods from 2019-2021. There are several tests used in this study descriptive statistical test, classical assumption test. In addition, the analysis method used is multiple regression analysis. Because in the literature, there is still much that needs to be developed regarding variables or factors that cause fiscal stress. The research results obtained are regional income, debt usage and service level flexibility simultaneously have a positive effect on fiscal stress in districts and cities in North Sumatra Province. Regional income with an indicator of the independence ratio partially has a negative effect on fiscal stress and the intergovernmental ratio partially has a positive effect on Fiscal Stress in districts and cities in North Sumatra Province. The use of debt partially has a negative effect on fiscal stress in regencies and cities in North Sumatra Province and the flexibility of service levels partially has no significant effect on fiscal stress in regencies and cities in North Sumatra Province. This study develops a local revenue model using the independence and intergovernmental ratios that can be used by local governments in designing policies related to the management of their local revenues.